(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the frequency of hypertension in working and non- working women attending OPD of a Private sector hospital of Karachi. Study Design: Comparative Cross Sectional Study Place and Duration of Study: A comparative cross sectional survey of women visiting medical OPD was conducted in a private sector hospital of Karachi from January 2010 to November 2011. Materials and Methods: Study was conducted on working and non working women having age 20 years and above coming for treatment in OPD of a Private sector hospital of Karachi from January, 2011 to November 2011. Taking ethical consideration, data was collected by interviewing method. Besides socio-economic data, Blood pressure, weight and height were measured to calculate BMI for defining obesity. BMI more than 30 were considered obese. Data was analyzed by using statistical package SPSS version 16.0. Chi square test was applied to see the significance difference in both the groups at P<0.05. Results: Over all 540 women included in the study, 250(46.3%) were working women and 290 were non-working (53.7%). Among the working women 88(35.2%) were hypertensive whereas among non working women 173 (59.7%) were hypertensive (p<0.000). Most of the hypertensive working women were of the age group 40-49 years (44.4%) whereas hypertensive non working women were of age group 30-39 years. Among the working women 38% were obese while in non working women 56% were obese. Conclusion: Our study shows that hypertension and obesity is more common in non working women as compare to working women and its shows that it’s not the working which is the risk for developing hypertension rather there are other factors which increases the risk of hypertension and there is need of further studies.